Role of the acoustic phonon spectrum components in the formation of thermophysical properties of wurtzite-structure nanofilms - Lutsiuk, Yu.V.; Kramar, V.M.; Konstantynovych, I.A. (Vasyl Stefanyk Carpathian ational University : Ivano-Frankivsk, 2025)
The temperature changes of heat capacity, entropy, free energy, and coefficients of thermal conductivity and thermal diffusion of nanometer-thick planar structures (nanofilms) were investigated.
Keywords: lead diiodide, nanofilm, heat capacity, entropy, free energy, thermal conductivity, thermal diffusion